Informed and uninformed opinions on new measures to address climate change - Carola Kniebes; Christine Merk; Gert Pönitzsch; Katrin Rehdanz; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2014)
Climate engineering (CE) and carbon capture and storage sub-seabed (CCS-S) are currently controversially debated options to address climate change. Our paper provides empirical evidence on the public perception of two different CE measures, namely, stratospheric sulphate injection (SSI) and afforestation, as well as CCS-S. Using data from a novel large-scale survey, we analyse the determinants of acceptance of these measures in Germany. We also provide experimental evidence on how additional information on these measures changes the respondents' acceptance. We show that the acceptance differs strongly between the three measures. Afforestation is strongly favoured over CCS-S and SSI. This ranking holds independent of the amount of information provided. For all three measures, we find that, on average, additional information decreases acceptance. However, the sign and the strength of the information effect strongly depend on personal characteristics, such as gender and risk attitude.
Keywords: Q50; Q54; C83; D19; 330; Climate Engineering; Carbon Capture and Storage; Climate Change; Public Opinion; Survey